Analisis Usaha Pengolahan Susu Kerbau Menjadi Gulo Puan Di Desa Rambutan Kabupaten Banyuasin - Utami, Mega; Umikalsum, R.A.; Azmi, Nur (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This research aims to analyze the production costs, revenues, and income of the sugar palm sugar business, calculate the break-even point (BEP), and identify problems in the sugar palm sugar business in Rambutan Village. The research method is a survey method. The data used are primary and secondary data. The results of the study show that the production cost of gulo puan 3 N Zubir is Rp8,936,825/month, Makanan Bangsawan is Rp7,553,722/month, and Traditional Food is Rp6,148,175/month. So the average production cost of gulo puan business in Rambutan Village is Rp7,539,574/month. The income of gulo puan 3 N Zubir is Rp18,720,000/month, Makanan Bangsawan is Rp15,600,000/month, and Traditional Food is Rp12,480,000/month. So the average income of gulo puan business in Rambutan Village is Rp15,600,000/month. The income of gulo puan 3 N Zubir business is Rp9,783,175/month, Makanan Bangsawan is Rp8,046,278/month, and Traditional Food is Rp6,331,825/month. So the average income of the gulo puan business in Rambutan Village is Rp8,053,759/month. The BEP analysis obtained BEP Production of gulo puan 3 N Zubir 302.kg. Food of the nobility 255.kg and Traditional Food 206.kg. So the average BEP per unit of production of the gulo puan business in Rambutan Village is Rp254 cups. BEP Price of gulo puan 3 N Zubir Rp14,321, Food of the nobility Rp14,526, and Traditional Food Rp14,779. The average BEP price of the gulo puan business in Rambutan Village is Rp14,524/cup. So from the three businesses it is feasible to run. The problems faced by gulo puan entrepreneurs are 1). Internal problems, namely: Limited raw materials, Expensive raw material prices, Long manufacturing process, Lack of understanding and use of social media, Limited access, Limited knowledge about gulo puan among young people, The tools used are still simple. 2). External problems, namely: Lack of assistance from the government, Lack of training or coaching.